(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2011)
In writing a booklet to support inclusive practice we are well aware that many teachers have concernsabout students with disabilities in the mainstream. We appreciate the perspective that teaching one or more students with a disability ina typical class is just one of a number of challenges that include changes to the curriculum, public scrutiny of yourstudents’ performance inbasic subjects, and the requirement to meet the needs of students from diverse cultural, linguistic and social backgrounds. However, we remain positive and optimistic about teachers’ capacity to respond to diversity and manyare doing it with great success. Funding is an issue that concerns many teachers because funding criteria have not always included the students who are most challenging – those students who may not have a diagnosis of anything but whose learning and/or behavioural needs dominate time, attention and energy. Some teachers are concerned about additional administration and paperwork, the lack of time fornecessary consultation with colleagues, and insufficient support for providing an appropriate curriculum, particularly in secondary school.